R object-oriented programming: a practical guide to help you learn and understand the programming techniques necessary to exploit the full power R - Black, Kelly (Community experience distilled., 2014)
R is best suited to produce data and visual analytics through customizable scripts and commands, instead of typical statistical tools that provide tick boxes and drop-down menus for users. The book is divided into three parts to help you perform these steps. It starts by providing you with an overview of the basic data types, data structures, and tools available in R that are used to solve common tasks. It then moves on to offer insights and examples on object-oriented programming with R; this includes an introduction to the basic control structures available in R with examples. It also includes details on how to implement S3 and S4 classes. Finally, the book provides three detailed examples that demonstrate how to bring all of these ideas together.